Performance Analysis of a Portable Solar Panel Charging System for Urban Parks - FAHMI NORCAHYO Fahmi Norcahyo; Edy Susanto (DINAMIS, 2026)
The increasing use of portable electronic devices in urban parks has created a growing demand for independent and environmentally friendly charging facilities. This study aims to analyze the performance of a portable solar panel charging system under variations in solar irradiance, panel capacity, and panel configuration. Three irradiance levels (2.5, 4.5, and 5.5 kWh/m²/day), three panel capacities (100 Wp, 150 Wp, and 200 Wp), and three configurations (single panel, parallel, and series) were evaluated. Engineering-based energy calculations were validated using MATLAB/Simulink through the PV Array Model to analyze the current–voltage (I–V) and power–voltage (P–V) characteristics of the photovoltaic system. The results show that solar irradiance is the dominant factor affecting daily energy production. Under medium irradiance conditions (4.5 kWh/m²/day), the estimated daily energy outputs of the 100 Wp, 150 Wp, and 200 Wp panels were approximately 315 Wh/day, 472.5 Wh/day, and 630 Wh/day, respectively, while the highest energy output of 770 Wh/day was achieved by the 200 Wp panel under high irradiance conditions (5.5 kWh/m²/day). Among the evaluated configurations, the parallel arrangement provided the most suitable performance for portable charging applications because it delivered higher output current and improved battery charging capability. Based on the obtained results, a portable solar panel system with a capacity of 150–200 Wp in a parallel configuration is recommended for charging electronic devices in urban parks. These findings demonstrate that combining appropriate panel capacity, solar irradiance conditions, and system configuration can significantly improve the performance and practicality of portable photovoltaic charging systems for public outdoor facilities.